Performance of Two Novel Obesity Indicators for the Management of Metabolic Syndrome in Young Adults - Liu, Xiaoli; Ma, Chunpeng; Yin, Fuzai; Wang, Rui; Lu, Qiang; Lu, Na; Ma, Chunming (Frontiers in Endocrinology, 2021)
Background Metabolic syndrome (MetS) is a pathophysiological change based on the abnormal metabolism of many substances. The study aims to investigate the performance of visceral adiposity index (VAI) and lipid accumulation product (LAP) of MetS in young adults. Methods 448 young adults aged between 19 and 24 years old in Qinhuangdao had been included in this cross-sectional study. Receiver operating characteristic (ROC) curve analyses were used to assess the accuracy of these two obesity indicators for MetS. Results The prevalence of MetS was 2.0%. In male subjects, LAP had the highest area under the ROC curve (AUC) value (AUC = 0.963), followed by VAI (AUC = 0.937). In female subjects, LAP also had the highest AUC value (AUC = 0.931), followed by VAI (AUC = 0.861). No significant difference was found between the two obesity indicators (P > 0.05). Conclusion The two obesity indicators were valuable for the screening of MetS in young adults, and LAP was the simpler of the two.